Periodontitis may predict the use of prescription medicines later in life, a database study - Frankenhaeuser, Freja; Söder, Birgitta; Källmén, Håkan; Korpi, Esa R.; Meurman, Jukka H. (Frontiers in Pharmacology, 2023)
Medications used for the treatment of diseases also affect oral health. We investigated how having/not having periodontitis at baseline in 1985 was associated with purchases of medicines in the long term. The study paradigm is in the oral health-systemic health connections. We hypothesized that periodontitis links to purchases of medicines later in life. The study cohort consisted of 3276 individuals from the greater Stockholm area, Sweden. Of them, 1655 were clinically examined at baseline. Patients were followed-up for >35 years, using the national population and patient registers. The burden of systemic diseases and purchases of medicines were statistically analyzed comparing patients with (n = 285) and without (n = 1370) periodontitis. The results showed that patients with periodontitis had purchased more of certain medications than non-periodontitis patients. Periodontitis patients purchased significantly more drugs used in diabetes (p = 0.035), calcium channel blockers (p = 0.016), drugs acting on the renin-angiotensin system (p = 0.024), and nervous system drugs (p = 0.001). Hence, patients with periodontitis indeed had purchased specific medications statistically significantly more than the periodontally healthy ones. This indicates that periodontitis, over time, might increase the risk for systemic diseases with the subsequent need for medication.